Strategi Penguatan Kreativitas Seniman Ketoprak DIY dari Tahun 1999 hingga Tahun 2009 - Yudiaryani Yudiaryani; Wahid Nurcahyono; Sylvia Angreni Purba (Dance and Theatre Review, 2019)
Cultural identity in ketoprak performance should depart from all cultural products themselves. Strengthening the form of ketoprak performance in the middle of the era becomes important for artists in building their creativity. The strategy was designed so that people assume that ketoprak was theirs and able to be their representation. Based on the data collected, the number of groups, performances, and ketoprak artists in DIY were as follows. The number of groups in four districts and one municipality were 497 groups. The number of ketoprak showed from 1999-2009 was 145 times. The highest number of ketoprak groups was in Kulonprogo Regency, followed by Gunungkidul Regency, Bantul Regency, Sleman Regency, and finally the Municipality. The year 2005 was a milestone in the development of ketoprak to the present. The successful renewal of ketoprak shows can be seen by the number of shows which are 113 times over five years (from 2005 to 2009), which means that there were twenty ketoprak shows every year, and every month there were two ketoprak shows. The condition was triggered by several factors as follows. First, local government awareness to determined the icon of DIY tourism as part of globalization. Second, the awareness of artists to package performances that match the demands of the times. Third, awareness of the artistic layout strategy using symbolic and supported by Tobong ketoprak tricks. Fourthly, the influence of ketoprak humor and ketoprak R&D which still uses the style of play and jokes, causes the ketoprak show to be no longer a mere political tool, but a tool and place of friendship for the citizens. Fifth, the story was no longer based on myths, chronicles and legends, but penetrated the wayang story but with a more contextual interpretation of the story with the present. By seeing the many activities of ketoprak performances in DIY it can be said if ketoprak has become an icon of culture and tourism in DIY. Ketoprak performances tread its survival was no longer a traditional art, but has become a form of modernist art. Over the past ten years, the ketoprak show has experienced quite improved conditions. The vigilance of artists and audiences must be constantly reminded. The trick was to continuing to enhance the role of government as a protector of arts and culture. The ketoprak festival must continuing to be held continuously. Improving the skills of ketoprak artists must continuing to be sharpened. Of course the friendship between Ketoprak artists must continuing to be encouraged. Government’s appreciation for ketoprak artists must be increased.Keywords: identity; ketoprak; strengthening; globalization